Evaluasi Sistem Informasi Akuntansi Pembayaran Gaji di PT BAP untuk Meningkatkan Pengendalian Internal dan Minimalisasi Risiko Fraud - Muhammad Glenn Waluyo Rahardika Putra; Galuh Budi Astuti; Lis Lestari Sukartiningsih; Sielly Budi Prameswari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research aims to evaluate the design and implementation of the payroll accounting information system at PT BAP to enhance internal control and minimize fraud risks. Payroll is a sensitive cost component, requiring a reliable system to ensure accurate calculations and timely payments. The method employed is a qualitative descriptive study with a case study approach, utilizing data collected through interviews, observations, and documentation. The findings indicate that while PT BAP has established adequate separation of functions and hierarchical authorization, fraud vulnerabilities remain due to the use of manual recapitulation documents and high dependency on external approval processes (PT Freeport Indonesia) without a clear Service Level Agreement (SLA). This situation potentially leads to risks such as ghost employees, overtime manipulation, and payroll delays. The implications of this study emphasize the importance of adopting a digital-based accounting information system (HRIS) and integrating collaboration portals for automated data validation. Recommended procedural improvements include real-time synchronization between digital attendance and the payroll module, as well as strengthening task segregation to minimize risky manual interventions.